Obesity and Overweight among Students in Arabic Secondary Schools in Erbil City - hussein, Kareema (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): The aim of the study was to identify the prevalence of overweight and obesity in adolescence andto estimate the effect of socio- demographic and health behaviors that predicting obesity in adolescents.Methodology: A cross-sectional descriptive study was being carried out at three public Arabic secondaryschools in Erbil city from October 1st 2010 to January 30th 2011. A systematic randomly sample size of 461 studentswas selected.Results: In this study, the age of (46.2%, 122) of males students were ranged between (17- 18.9) years old comparedto females students (74.1%, 146) their age ranged between (15 -16.9) years old. About (3.4%, 9) of malesadolescents having overweight while all female adolescents were recorded as normal weight with significant associationbetween weight status and gender (p-value= 0.006). There were (0.5%, 1) overweight that watching TVduring eating but (3.1%, 8) was did not watching TV during eating with significant association between weight statusand watching TV during eating (p- value= 0.041).Recommendation: This study recommended placing posters throughout the school showing foods rich in variousnutrients, healthy food tips in the school news letter for parents and educational activities with more orientationabout their diet and physical exercise at early ages involving the whole family to control the excess of weight.Keywords: anthropometric measure weight status, adolescent, physical inactivity, fast food.